Reflections about an investigation research experience with capoeira - Alves, Flavio Soares [UNESP]; Carvalho, Yara Maria de (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2014)
The aim of this article is to describe the movements of an investigation experience with capoeira. This description underscores deviations and transgressions that testify to some propensity towards the becoming of the methodological trajectory. We seek to map the ways in which the proceedings were deconstructed and transformed during field research. We intend to understand how researchers involvement with fieldwork forces the regular principles of action to their limits, keeping the investigative attitude in the tension between the referential function which points to regular application of proceedings and the propensity towards becoming. The introduction of the intensive in the investigation relation is thus shown, and the record of that intensive nurtures this description.
Keywords: Methods; Cartography; Capoeira